Pengetahuan Swamedikasi Obat Analgetik Pada Masyarakat Desa Ladeh Kecamatan Depati VII Kabupaten Kerinci - Wahyu Tri Aldilas; Medi Andriani; Ruri Putri Makrisa (CV. ITTC INDONESIA, 2026)
Self-medication involves recognizing early symptoms of illness and disease, and selecting and using medications. The criteria for selecting medications for self-medication include those available without a prescription, such as over-the-counter medications, prescription medications from pharmacies, and the use of traditional medicines, whether purchased instant or homemade. Self-medication, or swamedication, is defined as the selection and use of medications by individuals to treat conditions or symptoms they recognize or diagnose themselves, and to obtain medications without a doctor's prescription for therapeutic purposes. This study aims to determine knowledge about self-medication for analgesics in Ladeh Village, Depati VII District, Kerinci Regency, Jambi. This study uses a quantitative descriptive method with prospective data collection and a sampling technique using purposive sampling of 77 people. Ladeh Village residents aged 18-30 years were 35 people (45.45%), 31-40 years were 19 people (24.67%), 41-50 years were 23 people (29.87%), Ladeh Village residents were male 45 people (58.44%) and female 32 people or (41.55%), the results of the questionnaire study showed that 77 respondents from Ladeh Village had a good level of knowledge of self-medication for analgesic drugs, 25 people (32.4%), quite good 32 people (41.5%) and poor 20 people (25.9%).The Ladeh Village community who had a good level of knowledge of self-medication for analgesic drugs was 25 people (32.4%), quite good 32 people (41.5%) and poor 20 people (25.9%).